Edukasi HIV/AIDS pada Masyarakat Kelurahan Batang Arau Kecamatan Padang Selatan - Suci Maisyarah Nasution; Putri Rahmadani; Dinda Aisyah Salsabila; Dhea Amelia; Laura Prissa Utama; Nadia Intan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
A counseling program to increase knowledge and reduce stigma. The counseling program, themed 'Bersama Kita BAHAGIA,' aims to educate the community on how to avoid unwanted diseases and how to deal with diseases like HIV/AIDS properly. In 2021, Padang has seen a high number of HIV/AIDS cases, making this counseling program crucial in reducing the risk of this disease. The study involved administering a pre-test to the participants, providing them with educational materials, asking questions, and conducting a post-test. The purpose of the pre-test and post-test was to compare the participants' knowledge before and after receiving the educational materials. The study was conducted with 11 mothers who practice gymnastics in RW 4 Batang Arau Village. The educational materials used in the study included leaflets and posters. The results of the post-test showed an 18,19% increase in target knowledge compared to the pre-test results, indicating that counseling has a positive effect on community knowledge about HIV/AIDS.